Gene Expression Profile of Mycobacterium leprae Contribution in the Pathology of Leprosy Neuropathy - Souza, Beatriz Junqueira de; Mendes, Mayara Abud; Sperandio da Silva, Gilberto Marcelo; Sammarco-Rosa, Patrícia; Moraes, Milton Ozorio de; Jardim, Marcia Rodrigues; Sarno, Euzenir Nunes; Pinheiro, Roberto Olmo; Mietto, Bruno Siqueira (Frontiers in Medicine, 2022)
Peripheral neuropathy is the main cause of physical disability in leprosy patients. Importantly, the extension and pattern of peripheral damage has been linked to how the host cell will respond against Mycobacterium leprae infection, in particular, how the pathogen will establish infection in Schwann cells. Components of the dead bacteria are also capable of triggering the pathological process, generating a pro-inflammatory microenvironment that culminates in nerve degeneration. Conversely, viable M. leprae infection provokes an anti-inflammatory infection profile, promoting transcriptional modifications that allow the bacteria to survive through the use of the host cell's internal machinery. However, it has been reported that viable M. leprae are also involved in triggering reactional episodes that contribute to progressive neural damage in patients. Understanding the pathognomonic characteristics mediated by viable and dead M. leprae are essential for elucidating leprosy disease and its associated reactional episodes. Moreover, the impact of the viable and dead bacteria in Schwann cells is largely unknown and their gene signature profiling has, as yet, been poorly explored. Therefore, in this study, we analyzed the early differences in the expression profile of genes involved in peripheral neuropathy, dedifferentiation and plasticity, neural regeneration, and inflammation in Schwann cells infected with viable and dead M. leprae. We substantiated our findings by analyzing and comparing these modifications in gene expression with results obtained from human nerve biopsies of leprosy and non-leprosy patients, accompanied with histopathological analysis.